2022
DOI: 10.11591/eei.v11i5.3698
|View full text |Cite
|
Sign up to set email alerts
|

The impact of training data selection on the software defect prediction performance and data complexity

Abstract: Directly learning a defect prediction model from cross-project datasets results in a model with poor performance. Hence, training data selection becomes a feasible solution to this problem. Limited comparative studies investigating the effect of training data selection on the prediction performance have presented contradictory results. Those studies also did not analyze why a training data selection method underperforms. This study aims to investigate the impact of training data selection on the defect predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, software testing activities are higly expensive [1]. Numerious studies found that most software errors are caused by only some few parts of the software modules [2], [3]. To reduce the number of resources required for testing the software project, prior to testing activities, software testing team can use software defect prediction (SDP) tools to predict defect-prone modules in software projects [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, software testing activities are higly expensive [1]. Numerious studies found that most software errors are caused by only some few parts of the software modules [2], [3]. To reduce the number of resources required for testing the software project, prior to testing activities, software testing team can use software defect prediction (SDP) tools to predict defect-prone modules in software projects [4].…”
Section: Introductionmentioning
confidence: 99%